Analysis of the Challenges of Sustainable Organizational Development in a Changing Business Environment - Wijayanto, Ahmad; Panus, Panus; Hamdat, Aminuddin; Rizal, Muhammad; Salam, Karta Negara (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines the challenges organizations face in implementing sustainable development strategies within a rapidly evolving business environment. It examines key barriers, including regulatory constraints, financial limitations, technological adoption difficulties, and organizational resistance, while assessing the roles of leadership, governance, and innovation in fostering sustainability. Research Method: This study adopts a Systematic Literature Review (SLR) approach, synthesizing existing research from peer-reviewed academic sources to analyze sustainability challenges and strategic responses. The review integrates perspectives from Institutional Theory to understand how external pressures influence corporate sustainability practices. The study also considers empirical findings from recent literature to provide a structured evaluation of the factors affecting sustainability integration. Results and Discussion: The findings highlight that regulatory frameworks and market expectations are the primary drivers of sustainability adoption. However, many organizations struggle to balance short-term financial performance with long-term sustainability investments. The study identifies technological innovation as a key enabler of sustainable practices, but notes significant barriers, including high investment costs and skill gaps. Furthermore, effective leadership and corporate governance are critical in shaping organizational sustainability cultures. Implications: This study provides practical insights for businesses, policymakers, and researchers, highlighting the importance of integrated sustainability strategies that extend beyond mere compliance. It calls for enhanced regulatory alignment, cross-sector collaborations, and investment in digital sustainability solutions to drive long-term resilience. Future research should explore sector-specific sustainability challenges and the effectiveness of leadership models in driving sustainability transformation.